Neo-extractivism in Latin America : Socio-environmental conflicts, the territorial turn, and new political narratives - Svampa, Maristella (2019)
This Element analyzes the political dynamics of neo-extractivism in Latin America. It discusses the critical concepts of neo-extractivism and the commodity consensus and the various phases of socio-environmental conflict, proposing an eco-territorial approach that uncovers the escalation of extractive violence. It also presents horizontal concepts and debates theories that explore the language of Latin American socio-environmental movements, such as Buen Vivir and Derechos de la Naturaleza. In concluding, it proposes an explanation for the end of the progressive era, analyzing its ambiguities and limitations in the dawn of a new political cycle marked by the strengthening of the political rights.